DAMPAK TRANSISI DEMOGRAFI TERHADAP DEFISIT FISKAL DI INDONESIA - Jaka Sriyana (Economic Journal of Emerging Markets, 2008)
This paper attempt to examines the effects of the Ageing Population (AP) process on the public finance in Indonesia. As we know, Indonesia is one of the developing countries that experience the ageing population. In this case, the overlapping generation (OLG) framework is used to estimate the demographic transition and to simulate the effect of it to deficit budget. The results show that the aging process starts to kick in 2012. The ageing process has a significant impact to declining tax revenue and increasing government spending. They also show that the aging process puts an upward pressure on budget deficit. As a result Indonesia potentially faces a long-term threat to fiscal sustainability. Keywords: ageing, population, overlapping, spending, budge